TOWARDS GREATER LEARNER AUTONOMY IN FEEDBACK ON WRITING TASKS - Shakra, Zena Abu (European Scientific Journal, ESJ, 2013)
﻿﻿﻿This study explores the relationship between the concept of learner autonomy and feedback given on writing tasks in the second language (L2) setting. It takes on a linguistic perspective to demonstrate how learner autonomy may be fostered during writing conferences with L2 learners. It then examines the effect with such interaction has on L2 writers. Findings suggest that the attempt to generate autonomy during writing conferences results in learner composed goals which not only indicate evidence of reflectivity but also reveal instances of metalearning. More importantly, the study shows that writing instructors may often mistakenly presuppose that learners have reached their perspective on a writing revision at a point much earlier than expected. Hence, the instructor’s presupposition of the point at which the learner has truly understood the writing error needs to be revised since learners seem to become cognitively engaged at a point much later than after they claim understanding of the revision being made. The theoretical implications of how feedback may be an area of great potential for enacting learner autonomy are then discussed.